The Effectiveness of Group Counseling on Coping Strategy of Problem Focused Coping and Emotional Focused Coping to Increase the Assertive Behavior - Khabibi, Miftakhul; Sugiyo, Sugiyo; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2023)
Assertive behavior in social live affects the way individuals adapt to their new environment, society, and understand their own rights and others. The inability to do adaptation leads individuals to be passive and aggressive. Thus, the present study attempted to examine the effectiveness of group counseling with the coping strategy of problem focused coping and emotional focused coping to increase the assertiveness of SMK Astrindo students in Tegal City. It used an experimental study with randomized pretest-posttest comparison group design by involving 21 students as the subjects of the study whose data were collected using The Rathus Assertiveness Schedule (RAS) scale. Further, the collected data were analyzed using one way ANOVA. It resulted that all three experimental groups which used problem focused coping, emotional focused coping, and the combination of both achieved effectiveness in the assertiveness increase. Among three, the group with emotional focused coping appeared to get the most satisfying result indicated by the highest difference between pretest and posttest.